2019
DOI: 10.1097/mpg.0000000000002362
|View full text |Cite
|
Sign up to set email alerts
|

Real World Experience With Ustekinumab in Children and Young Adults at a Tertiary Care Pediatric Inflammatory Bowel Disease Center

Abstract: Background: Ustekinumab is an effective therapy for Crohn disease currently approved for adults. Off-label use in the pediatric population is increasing, but its effectiveness in this age group has not been reported. Aims: The aim of the study was to describe real-world experience with ustekinumab at a tertiary care pediatric inflammatory bowel disease (IBD) center. Methods: As part of an ongoing observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 22 publications
1
75
2
1
Order By: Relevance
“…UST is effective for treatment of Crohn's disease (CD) and ulcerative colitis 1‐4 . In addition to randomised controlled trials, multiple real‐world studies corroborated the effectiveness of UST in the treatment of CD 5‐19 . However, the risk of primary and secondary loss of response to UST has not been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…UST is effective for treatment of Crohn's disease (CD) and ulcerative colitis 1‐4 . In addition to randomised controlled trials, multiple real‐world studies corroborated the effectiveness of UST in the treatment of CD 5‐19 . However, the risk of primary and secondary loss of response to UST has not been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…18 Another recent study found that amongst 52 children with either CD or UC initiating ustekinumab, 50% of those previously exposed to anti-TNF treatment were in steroid-free remission by week 52. 19 Our results demonstrate the potential for mucosal healing in pediatric patients receiving ustekinumab. Furthermore, while in the other pediatric studies, all patients received maintenance doses of ustekinumab every 7-8 weeks, doses in our study were shown to be given as frequently as every 4 weeks in an attempt to optimize therapy prior to labeling a patient as a nonresponder, with no adverse effects noted.…”
Section: Discussionmentioning
confidence: 51%
“…[9][10][11][12][13][14][15] At present, limited data exists on ustekinumab use in pediatric CD, showing variable results. [16][17][18][19][20] We retrospectively describe 11 adolescent patients who received ustekinumab at the Montreal Children' s Hospital with the goal of assessing its efficacy in inducing clinical, biochemical, and endoscopic remission.…”
Section: Introductionmentioning
confidence: 99%
“…Ustekinumab fully human monoclonal antibody specifically binds to p40, common subunit of IL-12/IL-23, and neutralizes the bioactivity of IL-12/IL-23 which is closely associated with active IBD [15]. High concentrations of circulating ustekinumab by intravenous induction might effectively suppress IL-12/IL-23 pathway and lead to a prompt remission of responders [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…Ustekinumab, human monoclonal antibody that binds with high affinity to interleukin (IL)-12/IL-23p40 subunit induces clinical remission of refractory adult cases via the inhibition of cytokine production and inflammation [2]. However, the effectiveness in childhood IBD has not been established [3], and the applicability for pediatric cases remains elusive. The first-line biologics for the early-onset IBD are challenging to determine because TNF-α blockers often occur in association with infections and immunological disorders [4].…”
Section: Introductionmentioning
confidence: 99%